Densification effects of the carbon nanotube pillar array on field-emission properties. (31st May 2016) - Wang, Kuang-Yu; Chou, Chia-Hsin; Liao, Chan-Yu; Li, Yu-Ren; Cheng, Huang-Chung
Abstract: In this study, a simple densification method for carbon nanotube (CNT) pillars is proposed to achieve high-performance field emission characteristics and stable emission. Through capillary force during solution evaporation, the CNT density in each pillar can be increased by about six times without causing damage to the crystallinity of CNTs. The densified CNT pillars exhibit lower series resistance, sharper pillars, better contacts, higher thermal conductivity, and better mechanical stiffness than as-grown ones. Therefore, the threshold field of the field emitter with such CNT pillars of 50 µm height can be reduced to 1.98 V/µm, as compared with 2.2 V/µm for the undensified ones. Moreover, the fluctuation of field-emission current decreases from 15.5 to 9.4% after the stress tests at a field of 2 V/µm for 1800 s. These findings imply that the densified CNT pillars are promising for the field-emission applications.